Adsorption Behavior of Phenyl-Substituted Cyclopropanecarboxylic Acid on Al and Cu Surfaces: A Combined Experimental and First-Principles Study - Karakurt, Tuncay; Cukurovali, Alaaddin; Yilmaz, Ibrahim (Wiley, 2025)
The molecular structure of phenyl-substituted cyclopropanecarboxylic acid (PSCCA, C12H14O2; 3-methyl-3-phenylcyclobutane-1-carboxylic acid) was determined using nuclear magnetic resonance (NMR), infrared spectroscopy (IR), and X-ray crystallography techniques. Following structural confirmation, its molecular geometry was optimized at the Density Functional Theory (DFT) level. The van der Waals interactions were accurately accounted for using the DFT-D3 method in the CP2K program. Understanding the adsorption behavior of organic molecules on metal surfaces is of great significance for applications in catalysis, sensor design, surface functionalization, and corrosion prevention. In this context, the adsorption properties of the PSCCA molecule on Al and Cu surfaces were investigated in detail using DFT-based CP2K calculations. By optimizing different adsorption configurations, the binding energies of the most stable structures were calculated and compared. The obtained results indicate that the PSCCA molecule strongly binds to both Al and Cu surfaces, with a higher adsorption energy on the Al surface compared to the Cu surface. In addition, Mulliken population analysis revealed distinct electronic charge transfer characteristics upon adsorption, with substantially stronger electron transfer observed on the Cu(111) surface due to enhanced d-band-ligand orbital hybridization. This electronic behavior correlates with the adsorption strength and highlights the critical role of metal electronic structure in governing surface interactions. Electron density difference analyses suggest that PSCCA interacts with both surfaces via a physisorption mechanism. Furthermore, assessments in the context of surface inhibitor efficiency reveal that PSCCA has the potential to passivate active surface regions and hinder surface reactions. Analyses conducted under different pH conditions indicate that the inhibitory effect of PSCCA is particularly pronounced in acidic environments. These findings suggest that PSCCA, exhibiting higher adsorption energy and stability on the Al surface, can be considered an effective protective agent and may play a crucial role in the design of metal-organic interfaces.
Keywords: adsorption; CP2K; density functional theory (DFT); Gaussian; IR; metal surfaces; NMR; organic molecules; phenyl-substituted Cyclopropanecarboxylic acid; X-ray crystallography